Mergers and Acquisitions in India - Agarwal, Ankita (2008)
From the past few decades, Mergers and Acquisitions (M&A) have dominated the environment in which the companies operate. Various researches have also been carried out where the main focus of the study is on the abnormal returns of the acquirers of the firm after the merger. The results have revealed that on average, the returns to the target companies are positive and that they gain from mergers. However, the bidder returns may be zero or negative, but it still remains a puzzle if they gain from mergers in the long-run. This research investigates the performance of mergers and acquisitions and its impact on the returns of the acquirers of the firm. A study of 58 mergers and acquisitions of Indian targets during the period 2003-2008 was undertaken to examine the pre acquisition and post acquisition returns of acquirers in the long-term by assessing the extent to which share price performance was abnormal. The main target companies were based in India. The research methodologies, that is, event study methodology have been employed to assess the performance of acquirers after the merger activity. The results of the event study reveal that on an average, the acquiring companies experience a negative CAAR of -0.69%.